Pemberdayaan Siswa melalui Kerajinan Hand Craft Creatifity dari Sampah Anorganik di SMP Negeri 2 Paciran - Hidayatul Mufidah; Aliatin Zazila; Itmaamiyyatus Salima; Iva Muslikhah Alfianti; S Mahmuda; Siti Aminah; Silmi Nur Aida (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Every student must have a very large talent and most of the public high school girls in the az zakiyah dordoris performing in-house despairings from inorganic waste and at least two paciran high school students living in the az zakiyah dorm to develop his talent through inorganic garbage and so we can see the talent in developing inorganic waste Reducing the garbage to a good craft and junior state high school 2 packers located in az zakiyah dorm are already doing prndekatan's developmen base comunity developmen, or more familiar with abcd's application of deep-seated assets makes for a change in the social order Much of the country's high school, 2 pairs of young adults living in the az zakiyah dormitory and all of their administrators working together to achieve maximum results and to create a whole lot of creations, both in makeup and in money storage and in the creation of money and its creation are also very good and can be displayed in the show and at the state junior high school And the kids are so excited that we, too, are actually chaperoning the craft of an organic waste of garbage into a very good piece of work, and the children can put together to the full weight of it, and the board is also proud that the kids who go to middle school at az zakiyah are so highly skilled and we're so excited about having craft assistance From the inorganic garbage and we will also judge who is creatively organic is so good that we will be proud of a hadia where children are also happy in making hanky out of inorganic waste and serving successful dreams that az zakiyah has once seen